Molecular and cellular effects of insulin-like growth factor-1 and LongR3-IGF-1 on in vitro maturation of bovine oocytes: comparative study - Araujo, M. S. [UNESP]; Guastali, M. D. [UNESP]; Paulini, F.; Silva, A. N.; Tsunemi, M. H. [UNESP]; Fontes, P. K. [UNESP]; Castilho, A. C. S. [UNESP]; Landim-Alvarenga, F. C. [UNESP] (Churchill Livingstone, 2020)
Addition effects of insulin-like growth factor-1 (IGF-1) and its synthetic analogue insulin-like growth factor-1 recombinant-3 (LongR3-IGF-1) after in vitro maturation (IVM) of cattle cumulus-oocyte complexes (COCs) were compared and evaluated on meiotic progression, apoptosis and profile genes of oocyte competence (GDF9, BMP15, BAX, BCL2, OOSP1, IGFBP2, IGBFP4 and IGFBP5), and their respective cumulus cells (AREG, EGFR, FSHR, COX2, BAX, BCL2, IGFBP2, IGFBP4 and IGFBP5). The 739 COCs (n = 10 pools) of bovine ovaries were collected, selected and matured with IGF-1 (100 ng/mL), LongR3-IGF-1 (100 ng/mL), and in two control groups with 0.1% polyvinyl alcohol (PVA) or 10% fetal bovine serum (FBS), for 22-24 h. The statistical analysis was performed by a linear mixed effects model, ANOVA and Tukey tests. There was no statistical difference between experimental groups taken into account the meiotic progression and apoptosis (P > 0.05). Nevertheless, there were statistical differences (P = 0.05) among FBS, IGF-1 and LongR3-IGF-1 groups for IGFBP4 gene expression, and among PVA, IGF-1 and LongR3-IGF-1 for COX2 gene expression in cumulus cells. Moreover, statistical difference was found for BCL2 gene expression between IGF-1, FBS and PVA groups and for IGFBP4 gene expression between LongR3-IGF-1, PVA and FBS in oocytes. There was no statistical difference between experimental groups for other genes evaluated. These results showed a good performance of IVM of bovine oocytes in the presence of LongR3-IGF-1 and the possibility of replacement of IGF-1 and FBS.
Keywords: Oocyte; Cumulus cells; In vitro culture; Insulin-like growth factor-1; Gene expression